Effect of Solvent Composition on the Structural and Magnetic Properties of Mnzn Ferrite Nanoparticles Obtained by Hydrothermal Synthesis - Casagrande-Denardin, J (Springer Verlag, 2014)
Samples of manganese-zinc (MnZn) ferrites were successfully prepared by hydrothermal syntheses using different compositions of the reactive system (H2O)1-x :(EG)x (x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0), where EG = ethylene glycol. The samples were fully investigated by powder X-ray diffraction, Fourier transform infrared spectroscopy for both liquid and solid specimens, Mössbauer spectroscopy, vibrating sample magnetometer, and transmission electron microscopy. All the MnZn ferrites presented spinel phase and average particle diameters between 3.1 and 12.1 nm. The increase in the x values results in a decrease in the particle sizes. The FTIR spectra performed in liquid phase showed significant interaction between EG and metallic precursors used in the synthesis. Magnetic features as for instance saturation magnetization (MS) also decreases upon increasing the x values. In addition, all synthesized samples exhibited a superparamagnetic character at room temperature. The experimental methodology presented in this work is used to obtain superparamagnetic nanoparticles with controlled size (smaller than 13 nm) and morphology. © 2013 Springer-Verlag Berlin Heidelberg.